2009
DOI: 10.4103/0974-2727.54802
|View full text |Cite
|
Sign up to set email alerts
|

Hunt for the Hidden Trait

Abstract: Objective:To assess the efficacy of a peripheral smear examination as a screening tool for β-thalassemia trait.Materials and Methods:17 623 Leishman-stained peripheral smears were evaluated during the period from July 2006 to September 2007. The following parameters were studied: hemoglobin, red blood cell count, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration and red cell distribution width. All the cases that showed microcytosis, hypochromia, erythrocytosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Ansari SH et al conducted a study in Karachi, reported 62.2% siblings are β-thalassemia carrier in first family members of the patients [26]. In Bangladesh β-thalassemia minor were 21.3% [27] and in India 57 out of 60 inspected cases on peripheral smears were found to have same type of thalassemia trait [28]. The patients of BTT can also develop ID and they need iron therapy but differentiation in both diseases is necessary for their respective management to avoid serious consequences of iron overload on one side and to exclude severe hemoglobinopathy in developing fetus/newborn.…”
Section: Biostatistics and Biometrics Open Access Journalmentioning
confidence: 99%
“…Ansari SH et al conducted a study in Karachi, reported 62.2% siblings are β-thalassemia carrier in first family members of the patients [26]. In Bangladesh β-thalassemia minor were 21.3% [27] and in India 57 out of 60 inspected cases on peripheral smears were found to have same type of thalassemia trait [28]. The patients of BTT can also develop ID and they need iron therapy but differentiation in both diseases is necessary for their respective management to avoid serious consequences of iron overload on one side and to exclude severe hemoglobinopathy in developing fetus/newborn.…”
Section: Biostatistics and Biometrics Open Access Journalmentioning
confidence: 99%
“…Thalassemias, characterized by peripheral smear hypochromic microcytic anemia, are an autosomal recessive group of hematological diseases that result from the damaged structure of one or more of the hemoglobin chains 1 . Mutations in β-globin genes are the main factor in β-thalassemia 2 . Most often in βthalassemia, point mutations, small deletions or insertions into coding regions and exonintron junctions are found.…”
Section: Introductionmentioning
confidence: 99%